2009
DOI: 10.5194/angeo-27-4229-2009
|View full text |Cite
|
Sign up to set email alerts
|

Observational evidence for the plausible linkage of Equatorial Electrojet (EEJ) electric field variations with the post sunset F-region electrodynamics

Abstract: Abstract. The paper is based on a detailed observational study of the Equatorial Spread F (ESF) events on geomagnetically quiet (A p ≤ 20) days of the solar maximum (2001), moderate (2004) and minimum (2006) years using the ionograms and magnetograms from the magnetic equatorial location of Trivandrum (8.5 • N; 77 • E; dip lat ∼0.5 • N) in India. The study brings out some interesting aspects of the daytime Equatorial Electrojet (EEJ) related electric field variations and the post sunset F-region electrodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
1
25
1
Order By: Relevance
“…It was suggested that day's EEJ strength might be a very useful parameter for prediction of equatorial plasma bubbles and associated irregularities. The positive contributions of daytime EEJ parameters to the postsunset F region electrodynamics favorable for generation of irregularities are also supported by recent studies [ Sreeja et al , 2009; Uemoto et al , 2010]. Present paper deals with some case studies involving ESF and scintillation events in the context of variation of EEJ.…”
Section: Introductionsupporting
confidence: 65%
“…It was suggested that day's EEJ strength might be a very useful parameter for prediction of equatorial plasma bubbles and associated irregularities. The positive contributions of daytime EEJ parameters to the postsunset F region electrodynamics favorable for generation of irregularities are also supported by recent studies [ Sreeja et al , 2009; Uemoto et al , 2010]. Present paper deals with some case studies involving ESF and scintillation events in the context of variation of EEJ.…”
Section: Introductionsupporting
confidence: 65%
“…The strong eastward equatorial electric field during the pre-reversal enhancement is linked to another phenomena called equatorial spread-F or plasma bubble, which is characterized by a depletion of the equatorial ionospheric plasma density (e.g., Burke et al 2004;Stolle et al 2006). Attempts have been made by several authors (e.g., Sreeja et al 2009;Uemoto et al 2010;Hajra et al 2012) to find a link between geomagnetic daily variations and the occurrence of the equatorial spread-F. For example, Uemoto et al (2010) reported that the occurrence of the equatorial spread-F is reduced when the equatorial electrojet 1-2 hours prior to the sunset is westward. Their results suggest the possibility of the detection of the equatorial spread-F using ground magnetometer data.…”
Section: Eej Intensity and Equatorial F-region Parametersmentioning
confidence: 99%
“…This is a phenomenon that was measured with an enhancement of vertical drift at sunset and the activation of F region dynamo in the evening hour [Martinis et al, 2005;Sreeja et al, 2009;Adebesin et al, 2013a]. The vertical drift increases, reached a maximum peak at the start of eclipse, and decreases downward through the eclipse window close to zero drift thereafter.…”
Section: 1002/2015ja021557mentioning
confidence: 99%